Transforming growth factor beta 1 messenger RNA in Reed-Sternberg cells in nodular sclerosing Hodgkin's disease. Issue 2 (February 1995) - Newcom, S R; Gu, L
Abstract : AIMS--To determine the cellular origin of the most potent cytokine present in Hodgkin's disease, transforming growth factor (TGF) beta, the polycellular population of Hodgkin's tissue was studied using in situ hybridisation. METHODS--A biotin labelled oligo-complementary DNA (cDNA) was constructed according to the previously determined sequence for TGF beta 1 cDNA. Forty three frozen and paraffin wax embedded tissue samples replaced by Hodgkin's disease or non-Hodgkin's lymphoma, three Reed-Sternberg cell lines, one Ki1 positive lymphoma cell line, and an epithelial cell line were studied for expression of TGF beta 1 messenger RNA (mRNA) as well as secretion of the TGF beta 1 protein and expression of the CD30 epitope. RESULTS--The results obtained with the 24 frozen tissue samples confirmed that the TGF beta antigen is found predominantly in the nodular sclerosing Hodgkin's disease (NSHD) subtype. Nineteen paraffin wax embedded tissue samples were used to measure the simultaneous expression of CD30 and TGF beta 1 mRNA. The latter was found in eight of eight NSHD samples, two of six mixed cellularity samples, and two of five non-Hodgkin's lymphoma samples. No evidence of fibroblast expression of TGF beta 1 mRNA was noted. CONCLUSIONS--Activated lymphocytes in NSHD express TGF beta 1 mRNA, but binucleate Reed-Sternberg cells and mononuclear Hodgkin's cells are the primary sources of activated TGF beta in Hodgkin's disease.